2021
DOI: 10.5430/ijfr.v12n3p446
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanisms and Firm Performance in Saudi Arabia

Abstract: This paper examines the impact of corporate governance mechanisms including board size, independence, and meeting frequency, audit committee size and meeting frequency, CEO duality and ownership concentration on the operational, financial and market performance of Saudi listed firms using a contingent theoretical-based framework drawing on agency theory, stewardship theory and resource dependence theory. This study examines 210 listed Saudi Stock Exchange firms over the timeframe 2017 to 2019. The paper applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 100 publications
(195 reference statements)
7
42
0
3
Order By: Relevance
“…According to the findings of a number of studies that have been carried out, the board of directors of a firm need to have the greatest feasible membership. Some academics, such as Boshnak (2021) , have called for smaller boards, while others have supported larger boards, the latter of which would enable increased monitoring and improved decision-making. According to Boshnak (2021) , a modest board size may assist avoid social loafing and free-riding on larger boards.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the findings of a number of studies that have been carried out, the board of directors of a firm need to have the greatest feasible membership. Some academics, such as Boshnak (2021) , have called for smaller boards, while others have supported larger boards, the latter of which would enable increased monitoring and improved decision-making. According to Boshnak (2021) , a modest board size may assist avoid social loafing and free-riding on larger boards.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Some academics, such as Boshnak (2021) , have called for smaller boards, while others have supported larger boards, the latter of which would enable increased monitoring and improved decision-making. According to Boshnak (2021) , a modest board size may assist avoid social loafing and free-riding on larger boards. They found that this was more likely to occur on boards with larger surface areas.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The commissioners' role is expected to minimize agency problems that may arise between the board of directors and shareholders. Boshnak's (2021) show that board size and independence, audit committee, and meeting frequency negatively impact firm performance However, Man and Wong (2013) and Nasiri and Ramakrishnan (2020) stated that an independent board of commissioners significantly affects firm value. The existence of an independent board of commissioners is a useful control tool of company performance.…”
Section: The Proportion Of Independent Commissioners and Company Performancementioning
confidence: 99%
“…During audit committee meetings, the committee reviews the company's current year's performance and offer recommendations. Boshnak (2021) examined the impact of GCG mechanisms, including board size, independence, meeting frequency, audit committee size and meeting frequency, CEO duality, and ownership concentration on Saudi listed companies' operational, financial, and market performance. They show that board size and independence, audit committee, and meeting frequency have a negative impact on company performance.…”
Section: The Frequency Of Audit Committee Meetings and Company Performancementioning
confidence: 99%